Early manifestations of cystic fibrosis in a premature patient with complex meconium ileus at birth - Del Ciampo,Ieda Regina Lopes (2015)
OBJECTIVE: To report a case of a preterm infant with complex meconium ileus at birth and cystic fibrosis. CASE DESCRIPTION: A male infant was born by vaginal delivery at 33 weeks and 5 days of gestational age with respiratory distress and severe abdominal distension. The exploratory laparotomy in the first day of life identified meconium ileus and secondary peritonitis. Ileal resection and ileostomy were performed, followed by reconstruction of the bowel transit at 20 days of life. At 11 days of life, the first immunoreactive trypsinogen (IRT) was 154 ng/mL (reference value = 70), and oral pancreatic enzymes replacement therapy was started. After 23 days, the second IRT was 172ng/mL (reference value = 70). At 35 days of age he was discharged with referrals to primary care and to a special clinic for CF for the determination of sweat chloride. He was received in the outpatient clinic for neonatal screening for CF at 65 days of life presenting malnutrition and respiratory distress. The sweat chloride test was performed, with a positive result (126mEq/L). COMMENTS: This case illustrates the rapid evolution of CF in a premature patient with complex meconium ileus as the first clinical manifestation.